2013
DOI: 10.1002/glia.22482
|View full text |Cite
|
Sign up to set email alerts
|

The Neuregulin‐Rac‐MKK7 pathway regulates antagonistic c‐jun/Krox20 expression in Schwann cell dedifferentiation

Abstract: Schwann cells respond to nerve injury by dedifferentiating into immature states and producing neurotrophic factors, two actions that facilitate successful regeneration of axons. Previous reports have implicated the Raf-ERK cascade and the expression of c-jun in these Schwann cell responses. Here we used cultured primary Schwann cells to demonstrate that active Rac1 GTPase (Rac) functions as a negative regulator of Schwann cell differentiation by upregulating c-jun and downregulating Krox20 through the MKK7-JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 42 publications
2
62
0
Order By: Relevance
“…Age-dependent epigenetic change can play a role because it was shown that a decline in the brain remyelination with aging is an outcome of the progressive loss of HDACmediated repression (Shen et al, 2008). Our analyses showed that several of injury-activated genes affected by aging, including Fgf5, Bdnf, Gdnf, and Igfbp2 (Painter et al, 2014), are regulated by H3K27me3, which implies that there may be age-related impairment in the demethylation dynamics.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Age-dependent epigenetic change can play a role because it was shown that a decline in the brain remyelination with aging is an outcome of the progressive loss of HDACmediated repression (Shen et al, 2008). Our analyses showed that several of injury-activated genes affected by aging, including Fgf5, Bdnf, Gdnf, and Igfbp2 (Painter et al, 2014), are regulated by H3K27me3, which implies that there may be age-related impairment in the demethylation dynamics.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, ϳ50 -80% of Schwann cells are myelinating and the rest are nonmyelinating Schwann cells (Zorick et al, 1996;Topilko et al, 1997). For those genes expressed at very low levels in mature nerve, this would suggest, although not prove, that their expression is repressed in both Schwann cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of p75 NGFR on Schwann cells after injury are complex as p75 NGFR has roles in both Schwann cell apoptosis (Syroid et al, 2000) and myelination, depending on ligand presentation and intracellular binding partners (Cosgaya et al, 2002; Provenzano et al, 2008; Teng et al, 2005; Tep et al, 2012). Signaling through p75 NGFR can lead to activation of c-Jun-dependent downstream signaling pathways to regulate Schwann cell survival and differentiation (Lindwall Blom et al, 2014; Shin et al, 2013; Yeiser et al, 2004). Interestingly, c-Fos, which forms the AP1 transcription factor complex with c-Jun, was significantly upregulated in uninjured and 14dpi Cx32KO nerves, relative to WT.…”
Section: Discussionmentioning
confidence: 99%
“…Another pathway implicated in the Schwann cell's response to nerve injury is the ERK pathway. For example, induced activation of the Raf-ERK pathway results in induction of demyelination, and many of the genes induced by ERK activation (Mcp1/Ccl2, Cxcl10, Timp1, TGF␤1, and Megf10) appear to be distinct from c-jun-dependent genes (20,22). In particular, Ccl2 is a critical chemokine involved in recruiting macrophages to peripheral nerves after injury and in a peripheral neuropathy induced by a myelin gene mutation (78).…”
Section: Elf5(ets)mentioning
confidence: 99%